Hypoxia stimulates the migration and invasion of osteosarcoma via up-regulating the NUSAP1 expression - Zhang Ling (De Gruyter, 2021)
Osteosarcoma is a highly aggressive malignant tumor, which most commonly occurs in children and adolescents. This study aims to reveal that hypoxia promotes the invasion of osteosarcoma cells by up-regulating the expression of NUSAP1. The expression of HIF-1α and NUSAP1 was significantly up-regulated in MG63 cells cultured in hypoxia for 6–36 h. Furthermore, hypoxia induced the migration and invasion of MG63 cells and regulated the level of E-cad, N-cad, Vimentin, Snail, Slug, MMP2, and MMP9 proteins. Importantly, knockdown of NUSAP1 inhibited hypoxia-induced cell migration and invasion. In the hypoxia microenvironment, the addition of HIF-1α inhibitor or the transfection of siRNA specifically targeting HIF-1α significantly reduced the expression of HIF-1α and NUSAP1 and markedly inhibited the migration and invasion of MG63 cells under the hypoxia microenvironment. In conclusion, hypoxia induced the expression of NUSAP1 in a HIF-1α-dependent manner, stimulating the migration and invasion of MG63 cells.